2017
DOI: 10.1371/journal.pone.0169481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inulin on Proteome Changes Induced by Pathogenic Lipopolysaccharide in Human Colon

Abstract: In the present study, the protective role of inulin against lipopolysaccharide (LPS)-induced oxidative stress was evaluated on human colonic mucosa using a proteomic approach. Human colonic mucosa and submucosa were sealed between two chambers, with the luminal side facing upwards and overlaid with Krebs (control), LPS or LPS+ inulin solution. The solutions on the submucosal side (undernatants) were collected following 30 min of mucosal exposure. iTRAQ based analysis was used to analyze the total soluble prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Data from a recent study confirm the protective effect of inulin on LPS-induced colonic mucosal oxidative stress and muscle impairment. Using iTRAQ analysis, it was demonstrated that inulin restored the level of some important protective proteins involved in inflammatory processes, and it was able to avoid smooth muscle contraction impairment, preventing the LPS-dependent modification of some proteins involved in intestinal smooth muscle contraction [45]. Some of the most significant effects of inulin-type prebiotics are summarized in Table 1.…”
Section: Fructansmentioning
confidence: 99%
“…Data from a recent study confirm the protective effect of inulin on LPS-induced colonic mucosal oxidative stress and muscle impairment. Using iTRAQ analysis, it was demonstrated that inulin restored the level of some important protective proteins involved in inflammatory processes, and it was able to avoid smooth muscle contraction impairment, preventing the LPS-dependent modification of some proteins involved in intestinal smooth muscle contraction [45]. Some of the most significant effects of inulin-type prebiotics are summarized in Table 1.…”
Section: Fructansmentioning
confidence: 99%
“…On the other hand, incorporating inulin in a diet might exert beneficial systemic effects, despite the lack of desirable changes in the large intestinal environment and microbial activity [ 8 , 9 , 33 , 34 ]. As for the colon, recent findings have demonstrated that inulin alleviated negative effects of oxidative stress induced by lipopolysaccharide [ 11 , 12 ]. In the current study, no challenge was applied, which could increase the production of reactive oxygen species in the colon tissue of piglets above the basal level.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with former findings indicating decreased concentration of thiobarbituric acid-reactive substances, a biomarker of lipid peroxidation, in the liver of piglets fed inulin-supplemented diets [ 9 ]. The results obtained so far have indicated that, in the case of oxidative stress induced in the colon, inulin restored the level of DNA-(apurinic or apyrimidinic site) lyase [ 12 ], which is the DNA base excision repair protein and redox signalling factor maintaining transcription factors in an active reduced state [ 36 ]. This finding suggests that decreased excision activities in piglets resulted from the reduced level of DNA adducts and not from the decreased expression of genes encoding DNA repair enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin is non-digestible; therefore, passes throughout the small intestine and isfermented in the colon. Inulin may be able to feed and stimulate the growth and propagation of Bifi dobacteria species and other probiotics in the colon (Guarino et al 2017, Lightowler et al 2017, Lopes et al 2017, Valdés-Varela et al 2017, Vandeputte et al 2017.…”
Section: Introductionmentioning
confidence: 99%